A6_5 Man's Small Footprints - Doyle, Patrick; Schulz, William; Heaps, Jonathan; Minnis, Eden (Physics Special Topics, 2017)
In this report we analyse the feasibility of imaging the footprints left on the surface of the moon by Neil Armstrong in his 1969 moon landing. We find that a telescope roughly 1.5 km across would be needed to resolve the bootprints from earth, and a telescope of 13.7 km diameter would be needed to resolve the details of the bootprints. We then evaluate the distance at which a probe would need to orbit the moon to image the bootprints. We find a probe would need to orbit at 117 km to resolve the bootprints and 12.7 km to resolve the bootprints in detail.